Tempo do espírito e espírito do tempo: algumas observações mais ou menos intempestivas - Léa Freitas Perez (2018)
The text corresponds to the whole speech presented at the 29th International Congress of the Theology and Religion Sciences Society –Time of the Spirit: Inspiration and Discernment, on July 13, 2016, in the “Three Viewpoints about the Time of the Sipirit”Table. I wave some more or less untimely observations on the relationship between time of the spirit and spirit of time, with the aim to think about religiosity in the immediate contemporaneity. From a quick look at the technical vocabulary of the spirit tropefrom the way it is treated by Lalande on his Vocabulaire technique et critique de la philosophie(1968), the text notably dialogues, especially from Otávio Velho, with his book Mais realistas do que o rei: ocidentalismo, religião e modernidades alternativas(2007), with some religiosity facets in contemporaneity with the aim to think about the relations between religion and the culture of consumption and the communicative function of religion in times of globalization, of widespread communication, among others.